2012
DOI: 10.5897/ajmr12.1701
|View full text |Cite
|
Sign up to set email alerts
|

Presence and antimicrobial susceptibility of methicillin-resistant Staphylococcus aureus in raw and pasteurized milk and ice cream in Tabriz by culture and PCR techniques

Abstract: Reports of methicillin-resistant Staphylococcus aureus (MRSA) in food have become more frequent in recent years. The aim of this study was to estimate the presence of MRSA in raw milk, pasteurized milk and ice cream in Tabriz by culture and polymerase chain reaction (PCR) techniques, as well as the determination of their antimicrobial susceptibility. For this purpose, 300 samples of raw milk, pasteurized milk and ice cream were collected from different sellers in Tabriz. They were first evaluated for contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
6
16
3
Order By: Relevance
“…In accordance with our findings, Mirzaei et al (2011) did not detect the mecA gene in staphylocci isolated from 50 butter samples.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In accordance with our findings, Mirzaei et al (2011) did not detect the mecA gene in staphylocci isolated from 50 butter samples.…”
Section: Discussionsupporting
confidence: 80%
“…Kanaan and Al-Shammary (2013) found MRSA phenotypically in 6 (40%) of the 15 soft white raw cheese with whey samples. This study's results are similar to those of Arefi et al (2014) and higher than other researchers' results (Huber et al, 2010;Yücel and Anıl, 2011;Özpınar, 2011;Mirzaei et al, 2011;Can and Çelik, 2012;Kanaan and Al-Shammary, 2013). These differences may be due to variations in cheese-production technology, the number of samples, and the fact that the milk used in production was not pasteurized.…”
Section: Discussionsupporting
confidence: 78%
“…The thermostable endonuclease gene ( nuc gene) encodes the expression of the thermostable endonuclease enzyme, known to be an important pathogenic factor for S. aureus. The presence of such a gene in the genome of the staphylococcal cell increases the organism’s inherent capacity to initiate infection [1,6]. …”
Section: Introductionmentioning
confidence: 99%
“…The penicillin binding protein 2a (PBP2a) has a reduced affinity for beta-lactam antibiotics, resulting in resistance to most beta-lactam antimicrobial agents. Therefore, mec A or PBP2a are indispensable targets for methicillin-resistant staphylococci detection [6,13]. …”
Section: Introductionmentioning
confidence: 99%
“…In Iran, Mirzaei et al (2012) examined 300 samples (100 raw milk, 100 pasteurized milk and 100 ice cream) in 2010 and reported that 20 isolates (14 from raw milk, 6 from ice cream) carried the mecA gene, whereas Alian et al (2012) examined 348 raw milk samples from randomly selected herds between 2010 and 2011 and found a MRSA prevalence of 28%.…”
Section: Asia and Africamentioning
confidence: 99%